Peningkatan Motivasi Belajar Anak Pada Panti Asuhan Menara Kasih Indonesia Melalui Program “Motivasi dan Penghargaan” - Zebua, Okphilip Abdi Agam; Triani, Emi (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The author as a practitioner conducted a field work practicum (PKL) at the Menara Kasih Indonesia Orphanage. The field work practicum (PKL) conducted by the author was to research the problems experienced by the orphanage children. The problem experienced by the orphanage children was the lack of motivation in learning so that the children in the orphanage were less diligent in carrying out learning activities. From this problem, the author was interested and had the goal of increasing the learning motivation of the orphanage children which was a mini project of the author. The author has clients (groups) who experience this problem. The group consists of children who are still in grades 2 to 4 of elementary school (SD). The author uses the stages of social groupwork in his research from the preparation stage to the termination stage. The method used to find out the client's problems is by using Focus Group Discussion (FGD). After carrying out all the stages of social groupwork, the results presented by the author are so that the orphanage children experience increased learning motivation so that they have quality learning.